Apraisal of workplace Indoor Environmental Quality (IEQ) in office buildings at Penang Island - Othuman Mydin, Md Azree; Mohd Nawi, Mohd Nasrun; Che Munaaim, M. A. (Construction Research Institute of Malaysia (CREAM), 2017)
As the weather is quite a big challenge to Malaysia, thus the Malaysians are tending to create the living environment as comfortable as we can.Workplace environment is very important as it ensure the health, activeness and productivity of workers who work in there.To ensure an optimum working environment, the indoor environmental quality, or frankly said, the HVAC system plays a big role.The objective if this paper is to determine the current indoor environmental quality of the selected offices in Penang Island.A few parameters were determined such as temperature, humidity, air velocity, air flor, noise level and lighting condition.Through indoor environmental quality measurement, it is found that most of the offices facing the lighting and noise problem.